Vitamin B12 concentration and its association with sociodemographic factors in Colombian children: Findings from the 2010 National Nutrition Survey (2016)
Objective: Rapid changes in dietary patterns, economic development, and urbanization in low- to middle-income countries are fueling complex malnutrition states that need better characterization using population-level data. The aim of this study was to describe the key findings related to vitamin B12 status to identify the prevalence and associated sociodemographic factors in a representative sample of children in Colombia, based on the 2010 National Nutrition Survey. Methods: We analyzed cross-sectional data from 6910 Colombian children between the ages of 5 and 12. Serum vitamin B12 concentrations were determined by chemiluminescence. Sociodemographic data was assessed by computer-assisted personal interview technology. Results: Of the children assessed, 2.8% had vitamin B12 deficiency, defined as levels and lt;200 pg/mL, and 18.1% had marginal vitamin B12 deficiency, defined as levels between 200 and 300 pg/mL. A multivariate logistic regression analysis revealed increased risks for vitamin B12 deficiency among children ages ?9 y and for those living in the eastern, western, and southern regions of the country. No significant associations were found for ethnic groups, socioeconomic status, or urbanity levels. Being 11 y of age (odds ratio [OR], 2.16; 95% confidence interval [CI], 1.56-3.00; P = 0.0001), living in the west (Pacific) region of the country (OR, 3.92; 95% CI, 3.14-4.90; P = 0.0001), and being male (OR, 1.41; 95% CI, 1.20-1.65; P = 0.0001) were the factors most strongly associated with an increased risk for vitamin B12 deficiency. Conclusions: Compared with data from other Latin American countries, Colombian children have a lower prevalence of vitamin B12 deficiency; however the prevalence of marginal deficiency is substantial. Continued surveillance and implementation of interventions to improve dietary patterns among the high-risk groups identified should be considered. © 2016 Elsevier Inc.